A low-cost, low-intensity contingency management smoking cessation programme with students: Experimental evidence - Rusch, Olivia (School of Economics, 2019)
Tobacco consumption is a pressing global issue, leading to more than five million deaths each year. In South Africa, the smoking prevalence rate is stubbornly high, implying that a successful smoking cessation programme could have large social benefits, particularly if it targets young smokers. Contingency management interventions, which provide cash transfers conditional on biochemically-verified abstinence, have been effective in bringing about increased smoking cessation rates. However, contingency management programmes are typically very costly and involve frequent monitoring. This dissertation presents results of randomised controlled trial evaluating a low-cost, low-intensity contingency management smoking cessation programme conducted on a sample of treatment-seeking student smokers at the University of Cape Town in 2017. There is a statistically significant treatment effect, that is robust across multiple specifications, which increases the likelihood of abstinence by 13- 20%. In addition, the programme as a whole decreased the smoking intensity of non-abstainers. This study suggests, therefore, that a low-cost, low-intensity contingency management smoking cessation programme is efficacious in promoting abstinence amongst treatment-seeking students, and that it should be added to the tobacco control toolkit in South Africa.